Meiotic analysis of F1 hybrids among teosintes - González, Graciela Esther (2013)
The association of homologous or homeologous chromosomes in the meiotic behaviour of F1 hybrids reveals the relative affinity between genomes of parental species. Chromosomal rearrangements and genetic incompatibilities producing abnormal meiosis (abnormal spindle, laggard chromosomes, among others) acting as reproductive isolation mechanisms, could also be detected. In the present work the genome affinities based on the chromosome association of seven artificial hybrids among teosintes are discussed. Moreover, pollen stainability is reported.